2021
DOI: 10.1038/s41598-021-92839-z
|View full text |Cite
|
Sign up to set email alerts
|

Decreased ferroportin in hepatocytes promotes macrophages polarize towards an M2-like phenotype and liver fibrosis

Abstract: Iron release from macrophages is closely regulated by the interaction of hepcidin, a peptide hormone produced by hepatocytes, with the macrophage iron exporter ferroportin (FPN1). However, the functions of FPN1 in hepatocyte secretion and macrophage polarization remain unknown. CD68 immunohistochemical staining and double immunofluorescence staining for F4/80 and Ki67 in transgenic mouse livers showed that the number of macrophages in FPN1−/+ and FPN1−/− mouse livers was significantly increased compared to tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In contrast, macrophages also secrete anti‐inflammatory cytokines, such as transforming growth factor‐ β 1 (TGF‐ β 1) and IL‐4, which are the main modulators of the healing process after tissue injury. [ 54 ] Compared to the control group, the gene expression of TGF‐ β 1 and IL‐4 in the RQLAg group increased ( p < 0.01) (Figure 7D,E). In summary, the inflammatory characterization results show that the RQLAg hydrogel can reduce inflammatory cytokines, increase anti‐inflammatory cytokines at the wound site, and create a more favorable environment for wound repair.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, macrophages also secrete anti‐inflammatory cytokines, such as transforming growth factor‐ β 1 (TGF‐ β 1) and IL‐4, which are the main modulators of the healing process after tissue injury. [ 54 ] Compared to the control group, the gene expression of TGF‐ β 1 and IL‐4 in the RQLAg group increased ( p < 0.01) (Figure 7D,E). In summary, the inflammatory characterization results show that the RQLAg hydrogel can reduce inflammatory cytokines, increase anti‐inflammatory cytokines at the wound site, and create a more favorable environment for wound repair.…”
Section: Resultsmentioning
confidence: 99%
“…[36] In addition, a study reported that FPN deficiency-induced ferroptotic hepatocytes drove macrophage proliferation and M2 polarization by increasing IL-10 and TGF-b release concomitantly with aggravated liver fibrosis. [37] Ferroptotic cells can recruit macrophages by releasing cytokines. Monocyte chemoattractant protein-1 (MCP-1/ CCL2) is a key chemokine signal involved in fibrosis across multiple organs.…”
Section: Ferroptosis-mediated Necroinflammationmentioning
confidence: 99%
“…[36] In addition, a study reported that FPN deficiency-induced ferroptotic hepatocytes drove macrophage proliferation and M2 polarization by increasing IL-10 and TGF-β release concomitantly with aggravated liver fibrosis. [37]…”
Section: Evidence For the Involvement Of Ferroptosis In Fibrosismentioning
confidence: 99%